Case Report: A balloon-based technique to remove a pearl-like embolus out of the coronary artery - Wu, Kaimin; Chen, Xiang; Ding, Licheng; Wang, Bin (Frontiers in Cardiovascular Medicine, 2023)
Coronary embolism is considered as a rare non atherosclerotic etiology of acute myocardial infarction while atrial fibrillation is the main etiology of coronary embolism. We report a rare case of coronary embolism with a special pearl-like embolus attributing to atrial fibrillation. In this case, we used a balloon-based technique to remove the embolus out of the coronary artery successfully.